2014
DOI: 10.1111/jpi.12147
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves mitochondrial function in inguinal white adipose tissue of Zücker diabetic fatty rats

Abstract: Mitochondrial dysfunction in adipose tissue may contribute to obesity-related metabolic derangements such as type 2 diabetes mellitus (T2DM). Because mitochondria are a target for melatonin action, the goal of this study was to investigate the effects of melatonin on mitochondrial function in white (WAT) and beige inguinal adipose tissue of Zücker diabetic fatty (ZDF) rats, a model of obesity-related T2DM. In this experimental model, melatonin reduces obesity and improves the metabolic profile. At 6 wk of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 55 publications
5
52
1
1
Order By: Relevance
“…Chronic administration of melatonin is able to disrupt circadian homeostasis without affecting animals' behavior [40, 41]. However, in our study, we cannot discard that REM sleep deprivation may contribute to developing anxiety-like behaviors by disrupting circadian rhythm but, even in that case, melatonin can ameliorate these stress levels as shown by previous reports [6567]. Therefore, previous and current evidence help support the notion that melatonin may be considered as a possible therapeutic strategy when SD occurs [68].…”
Section: Discussioncontrasting
confidence: 47%
“…Chronic administration of melatonin is able to disrupt circadian homeostasis without affecting animals' behavior [40, 41]. However, in our study, we cannot discard that REM sleep deprivation may contribute to developing anxiety-like behaviors by disrupting circadian rhythm but, even in that case, melatonin can ameliorate these stress levels as shown by previous reports [6567]. Therefore, previous and current evidence help support the notion that melatonin may be considered as a possible therapeutic strategy when SD occurs [68].…”
Section: Discussioncontrasting
confidence: 47%
“…The dose of melatonin used (10 mg/kg/d) was selected based on previous studies. 36,37 Our results demonstrated that melatonin ameliorated lipid metabolism, hemodynamic and endothelial dysfunctions, and vascular hyperpermeability to a various extent in diabetic rats. Most importantly, our study is the first to show that the suppression of MLCK-and p-MYPT-mediated p-MLC expression, which was partly associated with the ERK/ p38 signal transduction pathway for the alleviation of hyperpermeability in both hyperglycemic and hypercholesterolemic states, played a crucial role in the protective effects of melatonin.…”
Section: Discussionmentioning
confidence: 90%
“…Fresh melatonin and vehicle solutions were prepared twice a week, and the melatonin dose was adjusted to the body weight throughout the study period. Drinking bottles were covered with aluminium foil to protect melatonin from light [25].…”
Section: Experimental Designmentioning
confidence: 99%
“…Melatonin, a pineal indolamine secreted in a circadian pattern, has well-known antioxidant [20,21] and anti-inflammatory effects [22,23], and it is involved in energy expenditure and body fat mass regulation [24,25]. Interestingly, it was shown that the amplitude of the nocturnal pineal [26] and serum [27] melatonin peaks decreases significantly in obese animals [28].…”
Section: Introductionmentioning
confidence: 96%